A Physiological Study of Albumin Level for Patients with Non-Hodgkin Lymphomas - Samer N. Khalaf (Journal of Global Pharma Technology, 2019)
Cancers cause increases in mortality in different countries each year. The late diagnosis of cancers contributes to patient death significantly. Recently, the efforts of scientists began towards examining several markers that help in early detection. This paper aims to monitor the relationship between serum albumin level and NHL beside some variables such as weight, age, sex and several other diseases. The demographic data and samples were collected from people with and without NHL. Then, the albumin concentration was assessed using the biochemical tests. After that, the data were analyzed statically using Minitab-16 program, T-test and ANOVA. The results showed a significant difference (P≤ 0.05) in albumin level between control and the patients with NHL. The same pattern was for patients with NHL and other diseases. In contrast, there was no considerable difference between male and female with NHL. Furthermore, the findings illustrated a decrease in albumin concentration for old patients' less than young patients. On the other hand, the overweight patients revealed more albumin level that the patients with normal weight. Serum albumin is considered an important sign for the early detection of NHL. This early diagnosis will play a good role beside the chemotherapy and other kind of treatment. This will help to reduce the risk and mortality because of cancers worldwide. Keywords: Non-Hodgkin lymphomas (NHL), Serum albumin level, Cancer, Overweight.